2001
DOI: 10.1097/00007890-200104150-00022
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Cross-Species Transmission of Porcine Endogenous Retrovirus Infection to Nonhuman Primate Recipients of Porcine Cells, Tissues, or Organs1

Abstract: These data suggest the absence of PERV infection in all 23 NHPs despite exposure to vascularized porcine organs or tissue xenografts and the use of immunosuppressive therapies in some animals. These findings suggest that PERV is not easily transmitted to these NHP species through these types of xenografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 35 publications
3
58
0
Order By: Relevance
“…These studies stand in contrast to the lack of infection detected in nonhuman primates (12)(13)(14)(15) and several small laboratory animal species (12,16). Similarly, it has not been possible to demonstrate PERV infection in patients exposed to living porcine tissues (17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 84%
“…These studies stand in contrast to the lack of infection detected in nonhuman primates (12)(13)(14)(15) and several small laboratory animal species (12,16). Similarly, it has not been possible to demonstrate PERV infection in patients exposed to living porcine tissues (17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 84%
“…islet cells, insulin, skin, extracorporal liver) for up to 12 years [42]. Recent intensive research has shown that porcine endogenous retroviruses probably do not present a risk for recipients of xenotransplants provided all necessary precautions are taken [43][44][45][46]. In addition, a strain of miniature pigs has been identified that does not produce infective PERV [47].…”
Section: Production Of a New Class Of Antibiotics: Cationic Antimicromentioning
confidence: 99%
“…However, co-culture of human cell line and cells from SNU miniature pigs showed that the virus was non-replicable and non-productive in human cells (7). Also, PERV has not been reported the infection to human and non-human primates in vivo (6,8,9).…”
Section: Introductionmentioning
confidence: 99%